2011
DOI: 10.1007/s00167-011-1546-5
|View full text |Cite
|
Sign up to set email alerts
|

Patellar chondral defects: a review of a challenging entity

Abstract: The optimal treatment for cartilaginous defects of the patella is still elusive. More prospective studies are needed, in order to identify which techniques are cost-effective especially on a long-term basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 56 publications
0
35
0
2
Order By: Relevance
“…16,18 Conversely, patients with PF cartilage lesions also more commonly undergo ACI instead of other treatments, such as OCA, MFx, and OAT, compared with patients with lesions in the femoral condyle. 19,20 A few factors contribute to this finding. As the shapes of the patella and trochlea are more highly variable than the condyles and plateaus, morphology matching is harder to achieve, particularly with the involvement of the central trochlear groove and median patellar ridge.…”
Section: Evaluation Of Outcomes and Long-term Recommendationsmentioning
confidence: 94%
“…16,18 Conversely, patients with PF cartilage lesions also more commonly undergo ACI instead of other treatments, such as OCA, MFx, and OAT, compared with patients with lesions in the femoral condyle. 19,20 A few factors contribute to this finding. As the shapes of the patella and trochlea are more highly variable than the condyles and plateaus, morphology matching is harder to achieve, particularly with the involvement of the central trochlear groove and median patellar ridge.…”
Section: Evaluation Of Outcomes and Long-term Recommendationsmentioning
confidence: 94%
“…The results of the clinical outcome measures in three patients may also be related to the additional procedures. However, especially realignment procedures are necessary in many cases to increase the probability for a success of cartilage repair in the patellofemoral joint [44]. A further limitation is that the structural architecture and cartilage specific extracellular matrix content of the repair tissue has not been evaluated histologically.…”
Section: Discussionmentioning
confidence: 99%
“…Penetration of the subchondral bone plate within the lesion leads to bleeding and subsequent fibrin clot formation, filling the defect and covering the exposed bony surface. Pluripotent, marrow-derived mesenchymal stem cells then migrate into the clot and promote the formation of a fibrocartilaginous repair tissue [34][35][36]. In a study of 68 patients with an average of 11.3 years follow-up status postmicrofracture, Steadman et al found significant improvement in pain and knee function at final follow-up [37].…”
Section: Cartilage Restorationmentioning
confidence: 99%